Characteristics of cold plasma treatment and enzymatic hydrolysis on IgG/IgE-binding ability of β-lactoglobulin. (December 2022) - Liu, Zhi-Wei; Zhang, Lin-Lin; Zhou, Ying-Xue; Tang, Pan-Pan; Tan, Yi-Cheng; Cheng, Jun-Hu; Mousavi Khaneghah, Amin; Aadil, Rana Muhammad
Abstract: Characteristics of cold plasma (CP) treatment and enzymatic (papain and alcalase) hydrolysis on IgG/IgE-binding ability β-lactoglobulin (β-LG) were compared, which is analyzed by immunoblot, WB, ELISA, and LC-MS/MS analysis. Results indicated that CP treatment exhibit similar characteristic to enzymatic hydrolysis to cleave the polypeptides chain of β-LG for reduction of its IgG/IgE binding ability. A similar tendency of decline in IgG/IgE binding capacity of β-LG after CP treatment was achieved in comparison with alcalase hydrolysis, which was reduced by 57.69% (IgG) and 56% (IgE) (for 4 min CP treatment) and 61.89% (IgG) and 27.54% (IgE) for alcalase hydrolysis (75 min), while no significant difference was detected for papain hydrolysis. Immunoblot and LC-MS/MS analysis confirmed that the antigenicity reduction was ascribed to the breakdown of the IgG/IgE linear epitopes of β-LG. Further combined with CP treatment (1 min) with alcalase hydrolysis (75 min), the reduction of antigenicity of β-LG reached 68.46% (IgG) and 59.26% (IgE). This study suggests that CP treatment is a promising alternative to enzymatic hydrolysis for hypoallergenic protein-producing. Highlights: CP exhibit similar characteristic to enzyme to cleave β-LG for reducing antigenicity. CP and Enzyme displayed different selectivity and specificity for cleavage site. Combined CP and alcalase treatment further reduce the antigenicity of β-LG.